Basic fibroblast growth factor helps protect facial nerve cells in a freeze-induced paralysis model. - Shinji Iwata; Hiroyuki Yamada; Masato Teraoka; Takemichi Tanaka; Takuya Kimura; Tomonori Joko; Yasuhiko Tabata; Hiroyuki Wakisaka; Naohito Hato (PLoS ONE)
Severe axonal damage in the peripheral nerves results in retrograde degeneration towards the central side, leading to neuronal cell death, eventually resulting in incomplete axonal regeneration and functional recovery. Therefore, it is necessary to evaluate the facial nerve nucleus in models of facial paralysis, and investigate the efficacy of treatments, to identify treatment options for severe paralysis. Consequently, we aimed to examine the percentage of facial nerve cell reduction and the extent to which intratympanic administration of a basic fibroblast growth factor (bFGF) inhibits neuronal cell death in a model of severe facial paralysis. A severe facial paralysis model was induced in Hartley guinea pigs by freezing the facial canal. Animals were divided into two groups: one group was treated with gelatin hydrogel impregnated with bFGF (bFGF group) and the other was treated with gelatin hydrogel impregnated with saline (control group). Facial movement scoring, electrophysiological testing, and histological assessment of facial neurons were performed. The freezing-induced facial paralysis model showed a facial neuronal cell death rate of 29.0%; however, bFGF administration reduced neuronal cell death to 15.8%. Facial movement scores improved in the bFGF group compared with those in the control group. Intratympanic bFGF administration has a protective effect on facial neurons in a model of severe facial paralysis. These findings suggest a potential therapeutic approach for treating patients with refractory facial paralysis. Further studies are required to explore the clinical applicability of this treatment.